Estimation of Plasma Arginine Vasopressin Concentration Using Thirst Perception and Plasma Osmolality Values (Nigerian Journal of Physiological Sciences, 2021)
Summary: In human, thirst and antidiuretic hormone (ADH) are controlled by similar sensitive osmoregulatory mechanisms such that above a certain osmotic threshold (280-288 mOsm/kg H20) there is a linear relationship between the increase in plasma osmolality and increase in ADH and thirst. The purpose of this study was to estimate plasma arginine vasopressin (PAVP) using thirst perception (TP) and plasma osmolality (POSM) values before and at 60 minutes in control or euhydrate (group A, 0.0 ml/kg body weight of distilled water), hydrated (group B, 7.1ml/kg body weight of distilled water) and dehydrated (group C, 0.0 ml/kg body weight of distilled water) subjects. A total of twenty five (25) subjects between the ages of 18 and 30 years were used for the study. Calculated POSM and TP values were used to estimate the PAVP concentration. Data were presented as Mean ± SEM. Analyses of results were done using ANOVA and Student t-test. The estimated values of PAVP using TP and POSM respectively at baseline levels were similar in euhydrate (2.22+2.00 vs 2.40+2.10 pg/ml), hydrate (2.22+1.34 vs 2.40+1.72 pg/ml) and in dehydrate (7.05+1.70 vs 6.92+1.94 pg/ml). Sixty minutes later, the values remained similar in euhydrate (3.29+2.40 vs 4.16+2.10 pg/ml), hydrate (1.92+1.60 vs 1.79+1.25 pg/ml) and in dehydrate (8.40+1.40 vs 9.20+1.50 pg/ml). The results show that there was a positive relationship between PAVP calculated from TP and POSM values. We therefore concluded that plasma arginine vasopressin concentration may be estimated using thirst perception and/or plasma osmolality values. Estimation of PAVP using plasma osmolar changes affected by glucose and urea may be inappropriate.